Influence of Metal Humic Complexes on Activity of Antioxidant System of γ-Irradiated Wheat Germs - Zohre Hanifa MUSLUMOVA (International Journal of Secondary Metabolite, 2016)
The activity of the antioxidant system of seedlings obtained from γ- irradiated seeds of wheat were investigated. The germination in high doses of ionizing radiation seed were reduced and the lipid peroxidation one week-old seedlings were stimulated. In the further development of seedlings, differences in the growth and activity of the antioxidant system was leveled. In case treatment with metal humic complexes (Na humate, K humate and Fe humate) the damaging effects of ionizing radiation on plants were reduced.